Impact and experience of participant engagement activities in supporting dapivirine ring use among participants enrolled in the phase III MTN-020/ASPIRE study - Garcia, Morgan; Luecke, Ellen; Mayo, Ashley J.; Scheckter, Rachel; Ndase, Patrick; Matovu Kiweewa, Flavia; Kemigisha, Doreen; Musara, Petina; Singh, Nishanta; Palanee-Phillips, Thesla; Baeten, Jared M.; Torjesen, Kristine; et al. (BMC public health, 2021)
Low adherence to investigational products can negatively impact study outcomes, limiting the ability to demonstrate efficacy. To continue advancing potential new HIV prevention technologies, efforts are needed to improve adherence among study participants. In MTN-020/ASPIRE, a phase III randomized, double-blind, placebocontrolled study of the dapivirine vaginal ring carried out across 15 sites in sub-Saharan Africa, a multifaceted approach to adherence support was implemented, including a strong focus on participant engagement activities (PEAs). In this manuscript, we describe PEAs and participant attendance, and analyze the potential impact of PEAs on ring use. Methods: All sites implemented PEAs and submitted activity and attendance reports to the study management team throughout the study. Participant demographics were collected via case report forms. Residual dapivirine remaining in the last ring returned by each participant was used to estimate drug released from the ring, which was then adjusted for time participants had the ring to calculate probable use categorized into three levels (low/intermittent/high). Product use was connected to PEA attendance using participant identification numbers. We used multivariate Poisson regression with robust standard errors to explore differences in ring use between PEA attendance groups and reviewed qualitative reports for illustrative quotes highlighting participant experiences with PEAs. Results: 2312 of 2629 study participants attended at least one of 389 PEAs conducted across sites. Participant country and partner knowledge of study participation were most strongly associated with PEA attendance (p < 0.005) with age, education, and income status also associated with event attendance (p <0.05). When controlling for these variables, participants who attended at least one event were more likely to return a last ring showing at least some use (RR = 1.40) than those who never attended an event. There was a stronger correlation between a last returned ring showing use and participant attendance at multiple events (RR = 1.52).
Keywords: new HIV prevention technologies; dapivirine ring